EFFECTIVE STRATEGIES FOR MAINTAINING MOTIVATION - Koyshekenova, T.; Tajetdinova, A. (ILIM hám JÁMIYET, 2016)
This article is about effective ways of maintaining students‘ motivation in teaching English. The author of the article emphasize, that teachers should integrate the motivational strategies in their classrooms and help their pupils make the most of their language learning.